Welfare State Change in Leading OECD Countries The Influence of Post-Industrial and Global Economic Developments - Schustereder, Ingmar J.; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
For decades, issues regarding the sustainability of the welfare state have been an important agenda in both academic and public debate. The existing literature primarily points out to economic globalization and post industrial developments as drivers behind recent welfare state change. Ingmar J. Schustereder investigates the relative influence of these factors and examines to what extent different national systems of social protection have preserved their core institutional features over time. He applies a combination of econometric and qualitative techniques using data of 17 leading OECD countries from 1975 to 2005.
The Welfare State and Welfare Capitalism -- Theoretical Foundations of the Welfare State -- Worlds of Welfare Capitalism: Interlinking Welfare State and Production Regimes -- Historical Development and Contemporary Challenges of the Advanced Capitalist Welfare State -- Historical Phases of Welfare State Development -- Post-Industrial Challenges of the Contemporary Capitalist Welfare State -- Economic Globalization and the Contemporary Capitalist Welfare State -- Empirical Analyses of the Driving Forces Behind the Contemporary Capitalist Welfare State -- Methodological Issues in Comparative Welfare Capitalism Research -- A Quantitative Study on the Determinants of Welfare Spending -- A Qualitative Study on the Recent Development Process of Advanced Capitalist Welfare States -- Summarized Findings and Conclusion.
Keywords: Economics; Economics/Management Science; Economics general